Neuroprotective and Disease-Modifying Potential of GLP-1 Receptor Agonists in Parkinson’s Disease: A systematic Review of randomized Controlled Trials and Cohort Study - Rizqiana Arum Sari; Habib Laksmana Prima; Faishal Hanif (International Journal of Health Engineering and Technology, 2026)
Parkinson’s disease (PD) remains a progressive neurodegenerative disorder without established disease-modifying therapy. Recent evidence links insulin resistance, mitochondrial dysfunction, and neuroinflammation to PD pathogenesis, suggesting that metabolic modulation may provide neuroprotective benefits. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs), initially developed for diabetes, have emerged as potential agents that may slow neuronal loss and improve motor function through pleiotropic neuroprotective mechanisms. This systematic review aimed to synthesize clinical and observational evidence on the efficacy and safety of GLP-1 receptor agonists in Parkinson’s disease, focusing on motor progression, non-motor outcomes, and mechanistic implications. A comprehensive search of PubMed, the Cochrane Library, and ScienceDirect was conducted up to October 2025 using the keywords Parkinson AND (exenatide OR liraglutide OR lixisenatide OR semaglutide OR GLP-1 receptor agonist) combined with (randomized OR trial OR cohort). Eligible studies included randomized controlled trials and cohort analyses involving adult PD patients treated with GLP-1 receptor agonists compared to placebo or standard therapy. Data were narratively synthesized due to inter-study heterogeneity. GLP-1 receptor agonists were well tolerated, with gastrointestinal discomfort and mild weight loss as the most frequent adverse events. Six studies met inclusion criteria: five randomized controlled trials and one large multi center cohort. Early-phase exenatide trials reported sustained motor improvements lasting up to twelve months after treatment cessation, while the Lixisenatide phase 2 trial showed significant slowing of motor decline. Conversely, the phase 3 Exenatide-PD3 trial showed no significant difference from placebo. Observational data involving over five million patients indicated reduced neurodegenerative risk, particularly among semaglutide users. GLP-1 receptor activation appears to exert neuroprotective effects through multiple mechanisms, including mitochondrial restoration, suppression of neuroinflammation, and improvement of neuronal insulin signaling. Differences in CNS penetration, receptor affinity, and treatment duration likely account for the variability in clinical outcomes. While results remain heterogeneous, the biological plausibility and reproducible direction of benefit across independent studies underscore the potential of metabolic intervention as a viable disease-modifying strategy in PD. Safety profile and consistent mechanistic rationale position this drug class as a leading candidate for future disease-modifying therapy in neurodegeneration. GLP-1 receptor agonists demonstrate emerging promise as neuroprotective agents capable of slowing Parkinson’s disease progression. Although definitive evidence of disease modification awaits further confirmation from large multi center phase 3 trials.